2014
DOI: 10.1111/ina.12162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of culture media and sampling methods onStaphylococcus aureusaerosols

Abstract: Staphylococcus aureus has been detected indoors and is associated with human infection. Reliable quantification of S. aureus using a sampling technique followed by culture assay helps in assessing the risks of human exposure. The efficiency of five culture media and eight sampling methods in recovering S. aureus aerosols were evaluated. Methods to extract cells from filters were also studied. Tryptic soy agar (TSA) presented greater bacterial recovery than mannitol salt agar (MSA), CHROMagar staph aureus, Chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The capture of S. aureus from exhaled breath with the BESS device but not filters could be attributed either to low recovery efficiencies for S. aureus from the filters, as reported elsewhere (Chang and Wang, 2015); or to sources of error such as contamination during sample handling or collection. S. aureus is a known commensal organism, thus prone to spread through contact easily.…”
Section: Discrepanciesmentioning
confidence: 69%
“…The capture of S. aureus from exhaled breath with the BESS device but not filters could be attributed either to low recovery efficiencies for S. aureus from the filters, as reported elsewhere (Chang and Wang, 2015); or to sources of error such as contamination during sample handling or collection. S. aureus is a known commensal organism, thus prone to spread through contact easily.…”
Section: Discrepanciesmentioning
confidence: 69%
“…Moreover, previous studies in dental offices sampled only the air of the consulting rooms which are largely contaminated by bioaerosols due to the widespread use of high-speed dental turbines, hand pieces, and mechanical scalers [41]; however, this study sampled the air in waiting and sterilization rooms. Finally, the use of a cyclonic liquid air sampler (Coriolis®µ) in this study could also partly explain this difference; other studies have used impactors to sample the air [46,47].…”
Section: Microorganisms: Bacteria and Fungimentioning
confidence: 98%
“…[9][10][11] A myriad of air samplers have been developed including adsorption tubes, passive badges, impactors, cyclones, and impingers. [12][13][14][15][16][17][18][19][20][21] Detailed reviews of the most popular conventional sampling techniques can be found in the works of Marple, 22 Henningson et al, 23 Kulkarni et al, 24 Chang et al, 25,26 and Ghosh et al 27 The impingement technique is one of the typical approaches in which airborne particles are collected in an extraction liquid. So far, different types of impingers have been designed; however, only a few of them, such as the All Glass Impinger 30 (Ace Glass Inc.) 10,25,26,[28][29][30][31][32][33][34] and the BioSampler (SKC Inc.), 10,25,26,[35][36][37][38][39][40][41] have been success-ful enough to be recognized as reference particle samplers in various applications.…”
Section: Introductionmentioning
confidence: 99%